STRATEGIES OF DIGITALIZATION IN THE CONTEXT OF BUSINESS DIGITAL TRANSFORMATION: TRENDS AND INNOVATIONS - PIROGOV, Dmytro; PIROGOV, Yehor; KUSHCH, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines the theoretical and practical foundations of modeling and forecasting in the context of complex economic systems, with a particular focus on the development of electronic commerce in Ukraine. Outtlines the conceptual basis of economic complexity and emphasizes the importance of mathematical and statistical approaches to understanding dynamic interdependencies in modern markets. The research highlights key modeling and forecasting methods such as econometric and mathematical models, regression analysis, ARIMA and VAR models. The article further investigates the use of these models in analyzing the evolution of e-commerce in Ukraine. Based on empirical data and statistical projections, it illustrates both the structural disruptions caused by external shocks and the subsequent recovery trajectories of the online trade sector.A separate section of the article is dedicated to current trends and future prospects of e-commerce in Ukraine. It is emphasized that successful forecasting and modeling of these dynamics are crucial not only for private businesses but also for shaping effective national digitalization policies.Overall, the article concludes that modeling and forecasting serve as indispensable tools for managing complexity in the digital economy.
Keywords: e-commerce; modeling; forecasting; economic systems; digital transformation